2001
DOI: 10.1046/j.1365-2206.2001.00215.x
|View full text |Cite
|
Sign up to set email alerts
|

Age at placement and adult adopted people's experience of being adopted

Abstract: Older age at placement has long been recognized as a risk factor in successful adoption outcomes. The findings of the present study emerged as part of a larger study that looked at the adoption experiences and reunion outcomes of 472 adults who had either searched for or been sought by one or more of their birth relatives. As part of the investigation, adopted adults were asked to evaluate their adoption experience. Age at placement was used as a key variable in examining whether or not adopted people felt dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 16 publications
1
10
0
2
Order By: Relevance
“…Children who are at greater risk for unsuccessful adoption outcomes include: (a) older children (Moffatt & Thoburn, 2001;Howe, Shemmings, & Feast, 2001;McDonald et al, 1991); (b) male children (Rosenthal, Schmidt, & Conner, 1988); (c) children with a history of multiple placements (Barth & Berry, 1988;Festinger, 1986;McDonald et al, 1991); (d) children with a history of physical abuse, deprivation, and neglect (Barth & Berry, 1988;Festinger, 1986;McDonald et al, 1991); (e) children with a history of sexual abuse and sexual acting out (Barth & Berry, 1988;McDonald et al, 1991Rosenthal et al, 1988, and; (f) children with emotional and behavioral problems (Barth, 1988;Barth & Berry, 1988McDonald et al, 1991). McGlone et al (2002) identified the importance of assessing parental readiness to adopt special-needs children.…”
Section: Discussionmentioning
confidence: 99%
“…Children who are at greater risk for unsuccessful adoption outcomes include: (a) older children (Moffatt & Thoburn, 2001;Howe, Shemmings, & Feast, 2001;McDonald et al, 1991); (b) male children (Rosenthal, Schmidt, & Conner, 1988); (c) children with a history of multiple placements (Barth & Berry, 1988;Festinger, 1986;McDonald et al, 1991); (d) children with a history of physical abuse, deprivation, and neglect (Barth & Berry, 1988;Festinger, 1986;McDonald et al, 1991); (e) children with a history of sexual abuse and sexual acting out (Barth & Berry, 1988;McDonald et al, 1991Rosenthal et al, 1988, and; (f) children with emotional and behavioral problems (Barth, 1988;Barth & Berry, 1988McDonald et al, 1991). McGlone et al (2002) identified the importance of assessing parental readiness to adopt special-needs children.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, their long‐term prospects for a durable and satisfactory placement are increased in that they are placed younger (Sellick & Thoburn 1996). Howe et al. (2001, p. 364) report that their ‘early placed group (before 12 months) were least likely to feel different to their adoptive family, and most likely to feel that they belonged, to feel loved by their adoptive mother and father, and to evaluate their adoption positively’.…”
Section: Findings About the Children And Their Parentsmentioning
confidence: 99%
“…However, research studies on international adoption have pointed to pre-adoption factors that may affect the emotional development of adopted children. The age at placement can be a protective or risk factor in the psychological adjustment of adopted minors (Erich and Leung, 2002;Howe, 1997;Howe, Shemmings, and Feast, 2001). The qualities of an adopted child's pre-placement care generally show a division between those who were adopted as babies (six months and younger) and those who were adopted as older children.…”
Section: Introductionmentioning
confidence: 99%